Long-Term Hand and Shoulder Function in Children following Early Surgical Intervention for a Birth-Related Upper Brachial Plexus Injury - Aber, Rachel N.; Grossman, Leslie A.; Berger, Aaron J.; Price, Andrew E.; Alfonso, Israel; Grossman, John A.I. (Journal of brachial plexus and peripheral nerve injury, 2024)
Purpose To better understand the long-term hand and shoulder outcomes of upper brachial plexus birth injuries. Methods We evaluated shoulder and hand function in 32 patients (13 males; 19 females) with a C5/C6 birth injury history). All patients had undergone primary nerve surgery as infants, and 12 underwent a simultaneous shoulder procedure as they presented with a fixed internal rotation contracture of the shoulder. On average, all patients were evaluated and examined 15 years postoperatively. The shoulder function was evaluated using the Miami Shoulder Scale. Hand function was measured by the 9-hole peg test (9-HPT) and statistical analysis included comparison of 9-HPT time against normative data using the Student's t-test. Results The cohort includes 22 right-hand-dominant and 10 left-hand-dominant patients. Mean age at surgery was 10 months; mean age at follow-up was 15 years ± 2 years 2 months. Cumulative shoulder function was “good” or “excellent” (Miami score) in 23 patients. For 9-HPT, 23 out of 32 patients seen had an involved hand with a significant alteration in function. Conclusion Early nerve surgery in cases of upper brachial plexus birth injuries result in the desired outcome. To ensure timely and targeted therapy for any residual deficits, it is imperative that limitations in hand function among children with an Erb's palsy.